Dopaminergic therapy removal differentially effects learning in schizophrenia and Parkinson’s disease - Weickert, Thomas W. (Schizophr Res, 2013)
Studies of patients with Parkinson’s disease receiving dopamimetics report conflicting evidence for early learning of probabilistic cue–outcome associations that elicits frontal–striatal activity. Previous studies of probabilistic association learning in patients with schizophrenia administered antipsychotics have displayed conflicting evidence for normal and abnormal learning. The role of dopaminergic treatment (dopamimetic versus dopamine antagonistic) effects on probabilistic association learning in these diseases that directly impact the dopamine system is not fully understood. The current study examined the effects of dopaminergic therapies on probabilistic association learning in 13 patients with schizophrenia and 8 patients with Parkinson’s disease under two conditions: after withdrawal from dopaminergic treatment and following administration of appropriate dopaminergic treatment. Medication order was counterbalanced in both groups. Patients with Parkinson’s disease failed to demonstrate any significant improvement over 150 trials, under both conditions (receiving or withdrawn from dopamimetics). Patients with schizophrenia withdrawn from antipsychotics displayed significant improvement during later trials only. These results demonstrate an effect of dopamine (DA) signaling on probabilistic association learning in that: (1) dopamine replacement therapy in Parkinson’s disease is insufficient to significantly improve probabilistic association learning and (2) DA receptor blockade impairs and removal of DA receptor blockade significantly improves frontal–striatal-dependent probabilistic association learning in schizophrenia, which is a novel finding and is opposite to the effects shown following removal of DA receptor blockade on other cognitive domains reported previously.